(Jihad and Violence in the Holy Quran, their dimensions are an intellectual study) (Journal of Imam Al-Kadhim College, 2023)
Abstract: All speeches whose roots are rooted in the Qur’an are far from the ideology and far from intellectual distortion and conceptual deviation and at the same time being close to the human being in all his diversity and differences. This is the active and influential factor in preserving the human being in his human capacity, dignity. And al-jihad in the Islamic religion is one of the ways to keep the presence and dignity of  human being  since it implies life as in  (  Punishment causes life for owners’ minds) because the supreme aim is to achieve the succession of man on earth.                                        As for the ideological discourse, which comes against human diversity in terms of his religion and thought, it begins to derive its components from violence, which is hatred for the other, exposing his dignity to humiliation, and this requires differentiating between the discourse of violence and the discourse of jihad
Keywords: jihad, violence, anthropology, Quranic vision